Thin capitalisation in South Africa, including a critical analysis of the Draft Interpretation Note on the determination of the taxable income of certain persons from international transactions - Beukes, Marvan (Department of Finance and Tax, 2016)
This dissertation endeavours to analyse the anti-avoidance measures implemented (and planned for the future) in South Africa to combat the practice known as "thin capitalisation". It critically analyses the Draft Interpretation Note on the determination of the taxable income of certain persons from international transactions: Thin capitalisation. It concludes that the arms-length approach is not suitable for South Africa and that it is essential that a system of advance pricing agreements be implemented.